Faktor-faktor yang Mempengaruhi Kinerja Karyawan Penyosohan Beras pada CV. Puspa di Kabupaten Jembrana - PRASANTI, ARETA RIZKA AYU; SURYAWARDANI, I GUSTI AYU OKA; SUDARMA, I MADE (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
Factors Affecting the Performance of Rice Processing Employees at CV. Puspa in Jembrana Regency. Human Resources (HR) is one of the important factors in improving company performance. This study aims to analyze the factors that affect employee performance. The study was conducted at the Rice Penyosohan at CV. Puspa in Jembrana Regency. The number of samples in this study were 95 people who were determined based on the provisions of the Structural Equation Modeling (SEM) Method. The data were analyzed based on the SEM method with the SmartPLS program. The results showed that, 1) Work compensation had a significant effect on the performance of rice milling employees at CV. Puspa, 2) Work motivation does not affect the performance of rice milling employees at CV. Puspa, and 3) Job satisfaction has a significant effect on the performance of rice milling employees at CV. Puspa. It is suggested that the company can improve the procurement of promotions and timeliness and the provision of wages or salaries that are in accordance with the position to improve employee performance.